Norma técnica e inserç\~ao internacional do Brasil: Novos desafios - Luís Fernando Tironi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This work focuses on two very particular elements: the technical standard and standardization that permeate the three determinants of the great changes in the international scenario in the last decades: the impact of new technologies on the commercial economic environment, the proliferation of preferential agreements between countries and the emergence of China as a major commercial economic power. Seen from this perspective, the global scenario for the brazilian insertion presents changes that mean transition to new paradigm and new challenges.
Keywords: F02; 330; technical standard; standardization; preferential agreements; innovation; China; economic development